Evaluasi Implementasi Metode Asuhan Keperawatan Profesional (MAKP): Scoping Review - Lindawati Br Barus; Wida Kuswida Bhakti; Dinarwulan Puspita; Suriadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: The Professional Nursing Care Model (PNCM) is a fundamental framework for organizing nursing delivery systems to enhance hospital operational efficiency and service quality. Despite its broad implementation in Indonesia, a comprehensive mapping of its evaluative outcomes and determining factors remains limited. This scoping review aims to systematically map scientific evidence regarding PNCM implementation, models, and determining factors within the Indonesian healthcare context. Methods: This review followed Arksey and O'Malley’s framework and PRISMA-ScR guidelines. A comprehensive literature search was conducted on PubMed, Scopus, ScienceDirect, and Google Scholar for studies published between 2016 to 2025. Eligibility was determined using the PCC (Population, Concept, Context) framework, focusing on studies evaluating PNCM impact in Indonesia. Results: Ten studies met the inclusion criteria. Findings indicate that PNCM implementation in Indonesia is largely adaptive, dominated by Team and Modified Team-Primary models. Overall implementation quality is categorized as